Economic Life of Coastal Communities: A Study of Meleura Beach Tourism Objects - Widya Astuti; Abdul Manan; Amar Ma’ruf (Journal La Lifesci, 2020)
This study aims to determine the impact of the Meleura Beach attraction for the economic life of the Lakarinta Coastal community, Lohia District, Muna Regency. This research was conducted using qualitative methods or purposive sampling techniques. The results showed that the local community felt a positive impact on the existence of this beach area, especially those directly involved with the development of Meleura beach tourism objects both economically. The development of Maleura Beach also has an economic impact, in the form of changes or shifts in the livelihoods of most Lakarinta villagers, from farmers to traders and service providers. Changes and/or transitions like this are followed by changes in community income which also shows an increasing trend. If before the beach was developed, the majority of residents who had jobs as farmers were only able to receive between Rp 1,000,000-5,000,000 per year, now on average they are able to receive more than Rp 10,000,000 per year, even some of them can receive more than Rp 100,000,000 per year. The need for solid government funding and community institutions to help improve the economic life of the community and help provide solutions that benefit the community.